P–598 Further evidence for a functional hormonal adrenal-ovarian axis affecting female infertility. (6th August 2021) - Benor, A; Molinari, E; Barad, D H; Gleicher, N
Abstract: Study question: How does here presented case offer further evidence for existence of a functional hormonal adrenal-ovarian axis? Summary answer: This is the first case of iatrogenic Cushing syndrome leading to severe adrenal and ovarian insufficiency, as evidenced by undetectable estrogen and low androgen levels. What is known already: Animal models and human data have convincingly demonstrated that hypo-androgenism affects follicle recruitment and growth, especially at small growing follicle stages, in most severe cases even mimicking primary ovarian insufficiency (POI). In milder forms, hypoandrogenism reduces follicle number, egg numbers as well as egg quality, unless reconstituted in timely fashion before IVF cycle start. Study design, size, duration: We here report a 34-year-old G1P1, who presented for a second opinion with a diagnosis of secondary "unexplained" infertility after two IVF cycles at another fertility center. Participants/materials, setting, methods: Since our center considers a diagnosis of "unexplained" infertility as subjective, the patient underwent a thorough diagnostic evaluation. She was using oral contraceptive pills for one week at the time her laboratory results were drawn. Main results and the role of chance: Her free (FT) and total testosterone (TT) (0.4 pg/ml and 5.0 ng/dL, respectively), DHEA and DHEAS (103.0 ng/dL and 92.0 µg/dL, respectively) were low and her estradiol was undetectable (<25 pg/mL), reflecting significant adrenal as well as ovarian suppression. Morning ACTH was undetectable at < 5 pg/mL but cortisol was abnormally elevated (17.7mcg/dL), leading to diagnoses of secondary adrenal insufficiency as well as secondary ovarian insufficiency (SOI) due to adrenal hypo-androgenism from lack of ACTH production. She, in addition, revealed a positive ANA titer (1:160). Because of eczema, she for over a year had been on a super-potent topical steroid ointment. Upon termination of this steroid, adrenal as well as ovarian function, as evidenced by her hormonal values, normalized. Limitations, reasons for caution: This is the first case in the literature where iatrogenic-induced insufficiency of adrenal androgen production resulted in secondary ovarian insufficiency (SOI), characterized by undetectable estradiol, reversible by withdrawal of topical steroid treatment. Wider implications of the findings: This case offers further evidence that the traditional hypothalamic-pituitary-ovarian axis (HPAA) extends downstream to ovaries (HPAOA), reaffirming the ability of adrenals to control ovarian function. Trial registration number: n/a